DAMPAK MENGKONSUMSI MONOSODIUM GLUTAMAT (MSG) DALAM PERKEMBANGAN OTAK ANAK - Diva Latifah Rochmah; Elisa Tri Utami (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Advances in information technology have an impact on changes in people's lifestyles, including changes in food consumption patterns that consume more types of fast food. Monosodium glutamate (MSG) is a flavor enhancer that is often used in cooking to enhance dishes. After being given a little vetsin, the food can be delicious because in the vetsin it contains sodium glutanic acid (glutanic acid sodium). Children's age or growth period is more sensitive to the effects of MSG than the adult group. Many people know about the dangers of monosodium glutamate and if they know the side effects of MSG, people should start reducing the use of MSG, but what happens is not as expected, many people still consume MSG in excess. The purpose of this study was to determine the dangers of Monosodium Glutamate (MSG) for body health and to determine the impact of consuming Monosodium Glutamate (MSG) on children's brain development. We used a research method in the form of secondary data. The results showed that the side effects of consuming foods containing MSG could indirectly make a person experience a decline in brain cognitive function.